2022
DOI: 10.21093/sajie.v4i2.4166
|View full text |Cite
|
Sign up to set email alerts
|

Can Islamic Stories be Used as Supplementary English Materials at Islamic Elementary Schools?

Abstract: Along with the Islamic schools’ vision and mission, their curriculum generally integrates Islamic values with all subjects taught at schools including the English subject. However, the implementation of the integration is still considered a challenge. This research aimed at confirming the possibility of Islamic stories being used as supplementary materials for English teaching at Islamic elementary schools and give an analysis of how to develop Islamic stories for English teaching materials. This research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…The use of teaching materials has a significant effect on the ability (Sadighi, Yamini, & Bagheri, 2018) especially integrated with the story. According to Ningsih, Oktriono, & Wiharja (2019) and Maesaroh, Aridah, & Rusmawaty (2022), eaching materials can be integrated with stories because they are seen as more interesting and motivating for students. Storybased teaching materials were also developed by Nazila, Adisaputera, & Saragih (2020) with a difference between pretest and posttest of 8.28 with a very good category so that it can be concluded that story-based teaching materials can improve learning outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The use of teaching materials has a significant effect on the ability (Sadighi, Yamini, & Bagheri, 2018) especially integrated with the story. According to Ningsih, Oktriono, & Wiharja (2019) and Maesaroh, Aridah, & Rusmawaty (2022), eaching materials can be integrated with stories because they are seen as more interesting and motivating for students. Storybased teaching materials were also developed by Nazila, Adisaputera, & Saragih (2020) with a difference between pretest and posttest of 8.28 with a very good category so that it can be concluded that story-based teaching materials can improve learning outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Antara watak-watak tersebut adalah isteri al-'Azīz, al-'Azīz, ahli keluarga Isteri al-'Azīz, wanita-wanita kota, banduan, Raja Mesir, ketua-ketua kaum dan para pembantu Menteri. Nama-nama mereka tidak disebutkan secara spesifik kerana tujuan kisah ini adalah untuk memberikan pengajaran kepada manusia (Maesaroh, Aridah & Rusmawaty, 2022).…”
Section: Skematik Pemilihan Watak Dialogunclassified
“…The ideology of Islamic values to spread goodness is one of the interesting topics for many researchers in the field of English language teaching (Damayanti, 2021;Hena, 2019;Irawan, 2020;Rohmah et al, 2019;Rohmana, 2020). Researchers are also interested in examining aspects of English language skills learning with Islamicthemed teaching materials or learning resources, namely listening skills learning (Baa & Jaya, 2018;Jaya et al, 2018), reading skills (Kusumaningputri, 2019;Sahyoni et al, 2021), Islamic materials, media, or learning resources (Djamdjuri et al, 2021;Maesaroh et al, 2022;Naralita & Azis, 2020;Shafwati, 2019). In addition, researchers are also interested in researching knowledge, culture, and the development of Islamic characters in learning English (Darmayenti et al, 2021;Farah et al, 2021;Ulyani, 2021).…”
Section: Introductionmentioning
confidence: 99%